Analysis of the Bipolar Resistive Switching Behavior of a Biocompatible Glucose Film for Resistive Random Access Memory. Issue 26 (15th May 2018) - Park, Sung Pyo; Tak, Young Jun; Kim, Hee Jun; Lee, Jin Hyeok; Yoo, Hyukjoon; Kim, Hyun Jae
Abstract: Resistive random access memory (RRAM) devices are fabricated through a simple solution process using glucose, which is a natural biomaterial for the switching layer of RRAM. The fabricated glucose‐based RRAM device shows nonvolatile bipolar resistive switching behavior, with a switching window of 10 3 . In addition, the endurance and data retention capability of glucose‐based RRAM exhibit stable characteristics up to 100 consecutive cycles and 10 4 s under constant voltage stress at 0.3 V. The interface between the top electrode and the glucose film is carefully investigated to demonstrate the bipolar switching mechanism of the glucose‐based RRAM device. The glucose based‐RRAM is also evaluated on a polyimide film to verify the possibility of a flexible platform. Additionally, a cross‐bar array structure with a magnesium electrode is prepared on various substrates to assess the degradability and biocompatibility for the implantable bioelectronic devices, which are harmless and nontoxic to the human body. It is expected that this research can provide meaningful insights for developing the future bioelectronic devices. Abstract : Glucose is investigated for the switching layer of resistive random access memory (RRAM). The glucose‐based RRAM shows nonvolatile bipolar resistive switching behavior with reliable stability. Biocompatibility of glucose‐based RRAM as an implantable bioelectronic device is realized using fully harmless electrodes and various substrates.